Analysis of the Management of IB Maslahah Children's Savings Products at BJB Syariah KCP Indramayu - Ilmatuz Zahro (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of sharia financial products in Indonesia is increasingly rapid, including the iB Maslahah Children's Savings offered by BJB Syariah. This product is designed to support people's financial literacy, especially children, by providing financial education from an early age. Through the wadiah yad dhamanah agreement, iB Maslahah Children's Savings offers various advantages, such as a low initial deposit, free administration fees, and easy access for parents to manage their children's savings. This research aims to analyze the effectiveness of managing iB Maslahah Children's Savings using qualitative descriptive methods. The research results show that the effectiveness of managing this product is influenced by several main factors, namely thorough financial planning, disciplined financial management, family financial readiness, and support from financial institutions. With proper implementation, iB Maslahah Children's Savings not only helps prepare children's future financially but also builds savings habits and financial understanding from an early age. It is hoped that this research can contribute to the development of sharia financial literacy in Indonesia and increase public participation in sharia-based financial products.